The Implementation of Early Warning Score for Early Detection of Death in Adult Inpatient Rooms - Wardah Fauziah; Novian Mahayu Adiutama (Babali Nursing Research, 2022)
Introduction: The Early Warning Score (EWS) can be used to predict the likelihood of short-term and long-term death. It is associated with abnormalities in the condition of vital signs of patients who are at high risk of death, regardless of the intervention or timeliness of medical personnel. Methods: This research is an innovation for the management of Evidence-based practice-based nursing actions. It was conducted using quantitative research (quasi-experiment) using post-test design with control group. The populations were all hospitalized patients in the adult room of the Subang Hospital. Results: The result showed that the Gross Death Rate in the control group of 29 people with a percentage of 10.54% of the total number of respondents is 275. Then, in the intervention group, the GDR figure was a small percentage of 12 people with a percentage of 4.36%. Meanwhile, the Net Death Rate in the control group was 9 people with a percentage of 3.27%. In the intervention group, the number of NDR was small, namely 4 people with a percentage of 1.45%. Conclusion: Based on the results and analysis of statistical tests that have been conducted on the implementation of the application of Early Warning Score (EWS), it was found that the detection of early death intervention group is lower than the control group. Early Warning scores significantly decreased the GDR and NDR in the intervention group compared to the control group.